NUSYUZ: ANTARA KEKERASAN FISIK DAN SEKSUAL - Faizah, Nur (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2013)
Nushuz is a classical conception of law that has been codified as standard the rule of law in the Compilation of Islamic Law (KHI). Some Muslims consider the explanation of the scholars about nushuz is taken for granted, mainly because it was labeled “religion” that is considered sacred and there is no room for change especially criticized. KHI is certainly not free from power, value s, and interests, in particular, of its the patriarchal apparatus of constituent, so women tend to be faced with a wall of injustice, subordination, masculine superiority and imbalance. This is reflected in provisions of nushuz in KHI that apply to the wife only and does not apply to husbands. Terms of nushuz in KHI also justify domestic violence, especially in the case of forced sexual intercourse by a husband against his wife. This article explains that in fact issue of nushuz is for husband and wife. However, the plains of empirical, KHI in explaining provisions of of nushuz apply to the wife only. This is where KHI has been marginalized and dehumanization of women.[Nusyu>z merupakan konsepsi hukum klasik yang telah terkodifikasikan sebagai aturan hukum baku dalam Kompilasi Hukum Islam (KHI). Sebagian umat Islam memandang penjelasan para ulama tentang nusyu>z merupakan hal yang terberi (taken for granted), terutama karena sudah diberi label “ajaran agama” sehingga dipandang sakral dan tidak ada ruang untuk mengkritisinya apalagi mengubahnya. KHI tentu tidak bebas dari kuasa, nilai, dan kepentingan, terutama, dari apparatus pembentuknya yang patriarkis, sehingga perempuan cenderung dihadapkan dengan tembok ketidakadilan, subordinasi, superioritas maskulin, dan ketidakseimbangan (dis-equilibrum). Hal itu tercermin dariketentuan nusyu>z dalam KHI yang hanya diberlakukan terhadap isteri saja dan tidak berlaku bagi suami. Ketentuan nusyu>z dalam KHI juga membenarkan tindakan KDRT, terutama dalam hal pemaksaan hubungan seksual oleh suami terhadap isterinya. Artikel ini memberikan penjelasan bahwa sebenarnya persoalan nusyu>z adalah bagi isteri dan suami. Namun pada dataran empirik, KHI dalam menjelaskan ketentuan nusyu>z hanya berlaku untuk isteri saja. Di sinilah KHI telah memarginalkan dan mendehumanisasi perempuan.]